Expanding (x+1)(x+3)
This expression is a product of two binomials, and we can expand it using the distributive property or the FOIL method.
Distributive Property
The distributive property states that a(b+c) = ab + ac. We can apply this to our problem:

Distribute (x+1) over (x+3): (x+1)(x+3) = (x+1) * x + (x+1) * 3

Distribute again: x * x + 1 * x + x * 3 + 1 * 3

Simplify: x² + x + 3x + 3

Combine like terms: x² + 4x + 3
FOIL Method
FOIL stands for First, Outer, Inner, Last, which helps us remember the order of multiplication:
 First: Multiply the first terms of each binomial: x * x = x²
 Outer: Multiply the outer terms of the binomials: x * 3 = 3x
 Inner: Multiply the inner terms of the binomials: 1 * x = x
 Last: Multiply the last terms of the binomials: 1 * 3 = 3
This gives us the same result as before: x² + 3x + x + 3 = x² + 4x + 3
Conclusion
Therefore, the expanded form of (x+1)(x+3) is x² + 4x + 3. This is a quadratic expression, meaning it has a highest power of 2.